Optometric Management of Concussion in Canadian Private Practice - Yeboah, Anne Marie; Dalton, Kristine; Irving, Elizabeth (Canadian Journal of Optometry, 2023)
Purpose The purpose of this study was to determine the current prescribing and assessment practices of optometrists in Canada seeing patients with persistent concussion-associated vision deficits. Methods A 6-question electronic survey was distributed to provincial and national boards of optometry in Canada. Questions pertaining to vision assessment, prescribing habits, daily living advice, appointment duration and follow-up appointment(s) were included. Practicing optometrists in Canada who have or have not managed concussion patients were eligible to complete the survey. Analysis consisted of categorizing and analyzing the frequency of responses provided. Results A total of 199 responses were received of which there were 142 completed responses (including 1 blank response). Of these, 13 optometrists indicated that they did not manage concussion. Of the 128 optometrists who indicated that they managed concussion 98% did a full eye exam. Visual acuity was assessed 96% of the time. Other frequent assessments were dry refraction 91%, pupil dilation 80%, and full binocular vision assessments 78%. Most respondents, 116, indicated that they provided advice on daily living activity and the most frequent advice was to limit activity, 64% (74/116). Responses were offered by 121 optometrists on appointment duration. Most frequently optometrists stated concussion appointments lasted between 30-60 minutes (69/121). Responses on follow-up were given by 119 optometrists and the most frequent follow-up was 1-2 months (27/119). Conclusion The results from this study provide insight on how optometrists in private practice are managing vision deficits following concussion. Further research on treatment effectiveness is required to develop an optometric protocol for the management of vision in patients with persistent concussion symptoms.